Macro X‐ray fluorescence imaging spectroscopy of the suggested Santi di Tito's portrait of Galileo Galilei. Issue 9 (9th January 2019) - Molaro, P.; Romano, F. P.; Tuniz, C.
Abstract : A painting of a bearded man on display at the Eremitani Museum in Padua that has been attributed to Jacopo Tintoretto has been suggested to be the lost portrait of Galileo Galilei painted by the Tuscan master Santi di Tito in 1602. Here, we present the X‐ray fluorescence (XRF) imaging spectroscopy of the painting in a search for elements that could help authenticate it. The XRF analysis demonstrated a typical palette of the 16th century consistent with both painters. However, the study demonstrated that the sitter had reddish hair and wore a coat that could be a gown. The original color of the eyes is not the present brown of the work, squaring with the light blue of Galileo's eyes in other portraits. There was a vermilion concentration under the left eye near a characteristic nevus on Galileo's face. This feature is in the copy of Santi di Tito's painting engraved by Giuseppe Calendi at the end of the 18th century, and thus consistent with evidence supporting the identity of the sitter as Galileo.